(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Hand, foot and mouth disease (HFMD) is a common infectious illness in children under five years old and can develop into outbreaks if preventive measures are ineffective. Mothers’ correct knowledge and practices play a crucial role in disease control. Objectives: To determine the proportion of mothers with correct knowledge and practices regarding HFMD prevention, and to assess the effectiveness of an intervention in improving knowledge and practices among mothers with children under five years old in kindergartens in Long Ho District, Vinh Long Province, in 2025. Subjects and Methods: A pre–post intervention study was conducted on 400 mothers whose children are attending kindergartens in Long Ho District. Data were collected using a standardized questionnaire on HFMD-related knowledge and practices. The intervention’s effectiveness was evaluated through active health education communication, using Chi–square analysis and the Effectiveness Index (EI), with statistical significance set at p<0.05. Results: After the intervention, the proportion of mothers with correct knowledge increased from 35.5% to 77.5%, with an Effectiveness Index of 118.3%; the proportion with correct practices increased from 39.3% to 79.5%, with an Effectiveness Index of 102.3% (p < 0.001). Conclusions: Health education interventions significantly improved HFMD prevention knowledge and practices among mothers with children under five years old. It is necessary to sustain and expand health education communication activities at kindergartens.